1995
DOI: 10.1161/01.cir.92.9.233
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Performance and Mass by Use of Cine MRI Late After Atrial Repair of Transposition of the Great Arteries

Abstract: Cine MRI allows quantitative evaluation of both RV and LV mass and function late after atrial repair of TGA. Longitudinal studies that include these measurements should prove useful in determining the mechanism of late RV failure in these patients. On the basis of these early data, inadequate hypertrophy does not appear to be the cause of late dysfunction in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
50
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 22 publications
10
50
0
1
Order By: Relevance
“…8,11 Volumes were measured by manually tracing the area of the endocardial and epicardial surfaces, respectively. The moderator band or other large trabeculae were included in the myocardial volume area.…”
Section: Assessment Of Rv and LV Volumes And Myocardial Massmentioning
confidence: 99%
See 2 more Smart Citations
“…8,11 Volumes were measured by manually tracing the area of the endocardial and epicardial surfaces, respectively. The moderator band or other large trabeculae were included in the myocardial volume area.…”
Section: Assessment Of Rv and LV Volumes And Myocardial Massmentioning
confidence: 99%
“…8 Increased ventricular mass was defined as a measure of ventricular hypertrophy. Myocardial mass was determined separately for the interventricular septum, RV, and LV free wall.…”
Section: Myocardial Hypertrophy and Rv Fiber Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In the long-term care of patients after atrial redirection surgery, clinicians are eager to understand the pathophysiology of reported late RV dysfunction, 8,9 reduced exercise capacity, 10 arrhythmia, and mortality from sudden cardiac death. [11][12][13] Multiple mechanisms for RV dysfunction late after atrial switch have been postulated.…”
Section: Introductionmentioning
confidence: 99%
“…THERE IS INCREASING DEMAND for an accurate method to evaluate right ventricular volumes and function, both in ischemic heart disease and in the follow-up of patients with congenital heart disease (CHD) (1)(2)(3)(4)(5). Established imaging modalities, such as echocardiography and tomographic-gated blood pool scintigraphy, are limited by the complex shape of the right ventricle (3,6).…”
mentioning
confidence: 99%